The Influence of Good Corporate Governance and Environmental Management Systems on ESG Risk Ratings: An Empirical Study of LQ45 Companies in Indonesia - Astria Putri Santosa; Dwi Jayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study critically examines the influence of Good Corporate Governance (GCG) and Environmental Management Systems (EMS) on Environmental, Social, and Governance (ESG) Risk Rating in LQ45 companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Elevated ESG Risk Ratings in several firms highlight ongoing challenges in managing sustainability-related risks, suggesting the need for more effective governance and environmental strategies. Using purposive sampling, a total of 9 companies were selected, yielding 36 observations. Data analysis was conducted through multiple linear regression using IBM SPSS Statistics 27. The findings indicate that GCG has a significant negative effect on ESG Risk Rating, implying that stronger governance practices contribute to lower ESG risk exposure. In contrast, EMS shows no significant effect. Nonetheless, both variables, when assessed simultaneously, exhibit a significant joint influence on ESG Risk Rating, underscoring their combined relevance in shaping corporate sustainability risk profiles.